Discerning the role of a functional arsenic-resistance cassette in the evolution and adaptation of a rice pathogen. Issue 7 (13th July 2021) - Kaur, Amandeep; Rana, Rekha; Saroha, Tanu; Patil, Prabhu B.
Abstract : Arsenic is highly toxic element to all forms of life and is a major environmental contaminant. Understanding acquisition, detoxification and adaptation mechanisms in bacteria that are associated with the host in arsenic-rich conditions can provide novel insights into the evolutionary dynamics of host–microbe–environment interactions. In the present study, we have investigated an arsenic-resistance mechanism acquired during the evolution of a particular lineage in the population of Xanthomonas oryzae pv. oryzae, which is a serious plant pathogen infecting rice. Our study revealed the horizontal acquisition of a novel chromosomal 12 kb ars cassette in X. oryzae pv. oryzae IXO1088 that confers high resistance to arsenate/arsenite. The ars cassette comprises several genes that constitute an operon induced in the presence of arsenate/arsenite. Transfer of the cloned ars cassette to X. oryzae pv. oryzae BXO512, which lacks the cassette, confers an arsenic-resistance phenotype. Furthermore, the transcriptional response of X. oryzae pv. oryzae IXO1088 under arsenate/arsenite exposure was analysed using RNA sequencing. Arsenic detoxification and efflux, oxidative stress, iron acquisition/storage, and damage repair are the main cellular responses to arsenic exposure. Our investigation has provided insights into the existence of a novel detoxification and adaptation mechanism within the X. oryzae pv. oryzae population to deal with high-arsenic conditions outside the rice plant.